Job satisfaction and leaving intentions of midwives: analysis of a multinational cross-sectional survey - Jarosova, Darja (2015)
To investigate the relationship between turnover intentions and job satisfaction among hospital midwives from seven countries and to determine how the related variables differ between countries.Studies investigating professional turnover and job satisfaction among midwives are limited in scope. A cross-sectional descriptive survey was used to investigate the intended turnover and job satisfaction relationship among 1190 hospital midwives in European and Asian countries. Data were collected using a set of questionnaires that included questions regarding the leaving intentions of midwives and the McCloskey/Mueller satisfaction scale. Midwives were least satisfied with their extrinsic rewards and professional opportunities and with the balance between family and work. Significant differences were found in all domains of job satisfaction according to midwives’ intentions to leave their current workplace in hospital or profession of midwife, and to work abroad. There are some general satisfying and dissatisfying elements for the profession of midwife across different countries. The results highlight the importance of understanding midwives’ leaving intentions and related factors across different countries. To prevent midwife turnover, health-care managers should gain greater insight into the early stage of midwives’ turnover intention.